Highly Diverse Shrub Willows (Salix L.) Share Highly Similar Plastomes - Wagner, Natascha D.; Volf, Martin; Hörandl, Elvira (Frontiers in Plant Science, 2021)
Plastome phylogenomics is used in a broad range of studies where single markers do not bear enough information. Phylogenetic reconstruction in the genus Salix is difficult due to a lack of informative characters and reticulate evolution. Here, we use a genome skimming approach to reconstruct 41 complete plastomes of 32 Eurasian and North American Salix species representing different lineages, different ploidy levels, and separate geographic regions. We combined our plastomes with published data from Genbank to build a comprehensive phylogeny of 61 samples (50 species) using RAxML. Additionally, haplotype networks for two observed subclades were calculated, and 72 genes were tested to be under selection. The results revealed a highly conserved structure of the observed plastomes. Within the genus we observed a variation of 1.68%, most of which separated subg. Salix from the subgeneric Chamaetia/Vetrix clade. Our data generally confirm previous plastid phylogenies, however, within Chamaetia/Vetrix phylogenetic results represented neither taxonomical classification nor geographical regions. Non-coding DNA regions were responsible for most of the observed variation within subclades and 5.6% of the analyzed genes showed signals of diversifying selection. A comparison of nuclear RAD sequencing and plastome data on a subset of ten species showed discrepancies in topology and resolution. We assume that a combination of (i) a very low mutation rate due to efficient mechanisms preventing mutagenesis, (ii) reticulate evolution, including ancient and ongoing hybridization, and, (iii) homoplasy has shaped plastome evolution in willows.